Prevalence of Vitamin A Deficiency (VAD) with Some Associated Risk Factors among Children Aged 1 to 5 Years in Rural Maharashtra – A Community Based Cross-Sectional Study - Raghavendra NR. Swamy; Priyanka N Akahade; P Abhinaya; Arvindkumar Waghmare; Satish V Gujalwar (Indian Journal of Community Medicine)
Background: Nutrition is an indispensable part of human life. Vitamin A deficiency(VAD) is the most important cause of preventable blindness in young children. It has long been a nutritional problem of public health significance in India and continues to be so. It is estimated that 50,000 preschool children become blind every year owing to VAD, and many of them will eventually die because of increased susceptibility to infections. To estimate the prevalence of clinical forms of vitamin A deficiency among the preschool children aged 1 to 5 years in the community and to determine the risk factors associated with vitamin A deficiency among the children aged 1-5 years. Material and Methods: This community based cross-sectional study was conducted among the pre-school children of RHTC area of a medical college between March 2019 to June 2019, IEC 24/2019. The data obtained was entered in MS-EXCEL 2010 and statistical software Epi info version 7. Results: The prevalence of vitamin A deficiency in our study was found to be 5.59%. On bi-variate analysis, the prevalence of vitamin A deficiency was more among the children belonging to class 4 and class 5 BG Prasad scale and was significant (p<0.05). According to our study grade 2 and grade 3 PEM, Diarrhoeal diseases, measles infection and lack of vitamin A prophylaxis has emerged as independent risk factors. Conclusion: Strengthening of immunization is very important to avoid VAD. Tailor made dietary modifications is very much essential among children, to combat PEM and in turn infections. Sources of vitamin A rich foods and its importance in a daily diet must be emphasized.